Beck Depression Inventory-II: Factor Analyses with Three Groups of Midlife Women of African Descent in the Midwest, the South, and the U.S. Virgin Islands. (4th March 2018) - Gary, Faye A.; Yarandi, Hossein; Evans, Edris; Still, Carolyn; Mickels, Prince; Hassan, Mona; Campbell, Doris; Conic, Ruzica
ABSTRACT: This research encompasses a factor analysis of the Beck Depression Inventory-II (BDI-II), which involves three groups of midlife women of African descent who reside in the Midwest, the South, and the U.S. Virgin Islands. The purpose of the study was to determine the factor structure of the BDI-II when administered to a sample of women aged 40–65 of African descent who reside in the three distinct geographical regions of the United States. A correlational, descriptive design was used, and 536 women of African descent were invited to participate in face-to-face interviews that transpired in community settings. Results of the factor analysis revealed a two-factor explanation. Factor one included symptoms such as punishment feelings and pessimism (cognitive), and the second factor included symptoms such as tiredness and loss of energy (somatic-affective). The application of the Beck Depression Inventory-II among the three groups of women generated specific information about each group and common findings across the groups. Knowledge gained from the research could help to guide specific intervention programs for the three groups of women, and explicate the common approaches that could be used for the three groups.